“Bimbingan Belajar” Peningkatan Literasi Siswa sebagai program kerja mahasiswa Universitas Hamzanwadi di SDN 2 Masbagik Timur - Uswatun Hasanah; Ulpatul Laeli; Shelly Alviani Utami; Ilma Karmila; Moh Yudi Nursyaid; Muhammad Husnan; Dina Apriana (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Education serves as a fondation for societal welfare, serving to foster knowledge and skills for meaningful contributions to community life. Through the Bina Desa Community Service Program (KKN) based on SDGs, Goal 4—quality education—students from the education faculty at Universitas Hamzanwadi aim to contribute by implementing literacy and numeracy tutoring programs. Students in grades 3, 4, and 5 who struggled with learning, especially in reading and writing, were identified through observations and teacher interviews. The tutoring program aimed to improve reading skills and motivate continuous learning, employing a personal approach through private sessions to tailor learning strategies. According to the findings, students' excitement for studying significantly increased. Additionally, instructive videos and thematic lectures were used to enhance students' literacy during the Sabtu Budaya lesson. The program's success in producing favorable results for kids was largely due to cooperation with teachers and the use of adaptive techniques.